Nickel-zinc battery with gas elimination structure

CN224908065UActive Publication Date: 2026-10-27DONGGUAN CHAO BA BATTERIES CO LTD SHENZHEN INNOVATION CENTER
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202521963938.3
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2025-09-12
Publication Date
2026-10-27
Estimated Expiration
2035-09-12

AI Technical Summary

Technical Problem

这些析出生成的氢气与氧气会在电池内部累积,不仅会导致电池内压异常升高,还会导致电解液因水分解而逐渐干涸,进而显著降低电池的循环寿命与充放电效率;更严重时,过高的电池内压可能引发电池壳体破裂、电解液泄漏,甚至对搭载设备造成不可逆的损坏,存在极大的安全隐患

Benefits of technology

[0026]1、本实用新型的具有消气结构的镍锌电池通过在卷绕空腔这一电池内部空间内置含有氢氧复合催化剂的消气结构,可直接对镍锌电池在充放电反应过程中产生的氢气和氧气进行消气处理。通过氢氧复合催化剂能够直接在电池内部环境下催化气体发生复合反应,避免气体在电池壳体内部积累,从根本上消除因内压过高导致的壳体膨胀、漏液甚至破裂等安全隐患,显著提升电池的使用安全性和可靠性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN224908065U_ABST
    Figure CN224908065U_ABST
Patent Text Reader

Abstract

The utility model discloses a nickel zinc battery with gas -removing structure, include: battery body and gas -removing structure, battery body includes battery roll core, and battery roll core has winding cavity, gas -removing structure is built -in in winding cavity, and gas -removing structure has hydrogen oxygen composite catalyst on, and hydrogen oxygen composite catalyst is used for catalyzing the hydrogen and oxygen that the battery body inside generates and generates composite reaction water. Thus, through directly building -in the gas -removing structure containing hydrogen oxygen composite catalyst in winding cavity, can hydrogen, oxygen that the charge -discharge process generates directly catalyzes as liquid water, can effectively avoid the gas accumulation in the battery, eliminates the shell expansion, breakage and so on security hidden danger, simultaneously, the water that generates can supplement electrolyte moisture, thereby can maintain ion transmission ability, ensures the battery charge -discharge function stability, prolongs the service life of battery, in addition, gas -removing structure is built -in in the original space, need not to change battery overall structure, does not occupy external volume, satisfies miniaturization demand.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This utility model relates to the field of battery technology, and in particular to a nickel-zinc battery with a degassing structure. Background Technology

[0002] The working principle of an alkaline nickel-zinc battery is based on the reversible redox reaction between a nickel hydroxide positive electrode and a zinc negative electrode in an alkaline electrolyte, achieving the interconversion between electrical energy and chemical energy. The nickel-zinc battery uses an aqueous solution of potassium hydroxide (KOH), sodium hydroxide (NaOH), and lithium hydroxide (LiOH) as the electrolyte, with a concentration between 30-55 wt.%. This electrolyte has high ionic conductivity, providing an effective channel for ion migration within the battery. During charging and discharging, hydroxide ions (OH-) in the electrolyte migrate directionally between the positive and negative electrodes and participate in the electrochemical reactions at the electrodes, thereby maintaining the overall charge balance of the system.

[0003] Currently, alkaline nickel-zinc batteries, as a highly promising type of aqueous energy storage device, have shown broad application prospects in many fields such as consumer electronics, portable power tools, automotive start-stop power supplies, data center backup power supplies, and large-scale energy storage systems due to their high energy density, high power density, intrinsic safety, environmental friendliness, and excellent charge-discharge cycle characteristics. However, nickel-zinc batteries suffer from serious gas evolution side reactions during charge-discharge cycles.

[0004] Specifically, nickel-zinc batteries typically have a charge / discharge window between 1.2 and 1.9V, and are charged using constant current and constant voltage modes. During charging, the main electrochemical reaction at the positive electrode is the conversion of Ni(OH)₂ to NiOOH, while the main electrochemical reaction at the negative electrode is the conversion of ZnO to Zn. When the battery is in a 1.9V constant voltage charging mode, gas evolution side reactions easily occur inside the battery. Generally, the positive electrode is more prone to oxygen evolution side reactions, while the negative electrode is more prone to hydrogen evolution side reactions. Furthermore, because metallic zinc is easily corroded in strongly alkaline environments, especially during high-temperature storage, it easily generates large amounts of hydrogen gas. It should be noted that under overcharge conditions, the Ni(OH)₂ positive electrode is extremely prone to oxygen evolution side reactions, and the ZnO negative electrode surface is particularly prone to hydrogen evolution side reactions. In addition, the charged zinc negative electrode, mainly composed of metallic zinc, is an amphoteric metal material, and in strongly alkaline electrolytes, it easily undergoes corrosion reactions, converting into zinc oxide or zinc hydroxide while generating large amounts of hydrogen gas. The main electrochemical reactions and gas evolution side reactions involved in the charging and discharging process of the positive and negative electrodes are summarized as follows:

[0005] The electrochemical reaction that occurs when Ni(OH)2 is charged is: Ni(OH)2 + OH- - →NiOOH+H2O+e -;

[0006] Gas evolution side reaction during charging / overcharging of Ni(OH)2 cathode: 4OH - →O2↑+2H2O+4e - ;

[0007] The electrochemical reaction that occurs when the ZnO negative electrode is charged is: ZnO + H₂O + 2e⁻ - →Zn+2OH - ;

[0008] Gas evolution side reaction during ZnO negative electrode charging / overcharging: 2H₂O + 2e⁻ - →H₂↑+2OH - ;

[0009] Two possible gas evolution side reactions at the zinc anode in the charged state:

[0010] Zn + 2H₂O → Zn(OH)₂ + H₂↑;

[0011] Zn + 2OH - →ZnO+H 2 ↑+2e - ;

[0012] Therefore, gas evolution side reactions mainly originate from the electrochemical decomposition of water molecules in the electrolyte and corrosion of electrode materials. The hydrogen and oxygen generated by these evolutions accumulate inside the battery, which not only leads to an abnormal increase in internal battery pressure but also causes the electrolyte to gradually dry out due to water decomposition, thus significantly reducing the battery's cycle life and charge / discharge efficiency. In more serious cases, excessively high internal battery pressure may cause the battery casing to rupture, electrolyte leakage, and even irreversible damage to the connected equipment, posing a significant safety hazard. Utility Model Content

[0013] The purpose of this invention is to overcome the shortcomings of the prior art and provide a nickel-zinc battery with a degassing structure, which can eliminate oxygen generated at the positive electrode and hydrogen generated at the negative electrode inside the battery, reduce the internal gas pressure of the battery, and prevent the electrolyte from drying out, thereby extending the cycle life of the nickel-zinc battery and preventing battery leakage.

[0014] The objective of this utility model is achieved through the following technical solution:

[0015] A nickel-zinc battery with a degassing structure includes: a battery body and a degassing structure. The battery body includes a battery core with a winding cavity. The degassing structure is built into the winding cavity and has a hydrogen-oxygen composite catalyst. The hydrogen-oxygen composite catalyst is used to catalyze the hydrogen and oxygen generated inside the battery body to undergo a composite reaction to generate water.

[0016] In one embodiment, the degassing structure includes a support, the hydrogen-oxygen composite catalyst is disposed on the surface of the support, or the hydrogen-oxygen composite catalyst is formed into the support by a granulation process.

[0017] In one embodiment, the carrier is a tubular structure.

[0018] In one embodiment, the support has an inner wall and an outer wall, and the hydrogen-oxygen composite catalyst is attached to the inner wall and / or the outer wall.

[0019] In one embodiment, the sidewall of the carrier is provided with a plurality of ventilation holes.

[0020] In one embodiment, the diameter of the vent is 0.1mm-2mm.

[0021] In one embodiment, the shape of the outer contour of the cross-section of the carrier is adapted to the shape of the cross-section of the wound cavity.

[0022] In one embodiment, the shape of the outer contour of the cross-section of the carrier is circular, elliptical, or polygonal.

[0023] In one embodiment, the maximum dimension of the cross-sectional outer contour of the carrier is 2mm-8mm.

[0024] In one embodiment, the hydrogen-oxygen composite catalyst is a supported catalyst, a hydrophobic supported catalyst, a porous supported catalyst, or a hydrophobic porous supported catalyst.

[0025] Compared with the prior art, the present invention has at least the following advantages:

[0026] 1. This utility model discloses a nickel-zinc battery with a degassing structure. By incorporating a degassing structure containing a hydrogen-oxygen composite catalyst within the internal space of the wound cavity, the hydrogen and oxygen generated during the charging and discharging process of the nickel-zinc battery can be directly degassed. The hydrogen-oxygen composite catalyst directly catalyzes the recombination reaction of gases within the battery's internal environment, preventing gas accumulation inside the battery casing. This fundamentally eliminates safety hazards such as casing expansion, leakage, and even rupture caused by excessive internal pressure, significantly improving the battery's safety and reliability.

[0027] 2. The nickel-zinc battery with degassing structure of this utility model can ensure that the gas is quickly converted into liquid water by contacting the catalyst after it is generated, and then flows back to the electrolyte to replenish the water consumed by the electrolyte during charging and discharging, maintain the ion transport capacity of the electrolyte, and avoid the decline in charging and discharging performance caused by gas occupying space or water molecules in the electrolyte.

[0028] 3. The nickel-zinc battery with degassing structure of this utility model directly incorporates the degassing structure containing hydrogen-oxygen composite catalyst into the existing space of the winding cavity. This eliminates the need for additional exhaust devices on the outside of the battery or to occupy additional space in the casing. It makes full use of the winding cavity inside the battery, which not only does not affect the external size of the battery, but also meets the application requirements of miniaturization and compactness of the battery. Attached Figure Description

[0029] To more clearly illustrate the technical solutions of the embodiments of this utility model, the accompanying drawings used in the embodiments will be briefly described below.

[0030] Figure 1 This is a schematic diagram of the structure of a nickel-zinc battery with a degassing structure according to an embodiment of the present invention;

[0031] Figure 2 for Figure 1 A schematic diagram of a nickel-zinc battery with a degassing structure (without the casing);

[0032] Figure 3 for Figure 2 A schematic diagram of the structure of the battery core in the diagram;

[0033] Figure 4 This is a schematic diagram of the degassing structure in the first embodiment of the present invention;

[0034] Figure 5 This is a schematic diagram of the degassing structure in the second embodiment of the present invention;

[0035] Figure 6 A simplified diagram illustrating the method of introducing the degassing structure into the winding cavity of the battery core;

[0036] Figure 7 This is a schematic diagram of the battery core structure in another embodiment of the present invention;

[0037] Figure 8 For application Figure 7 A schematic diagram of the degassing structure of the battery core. Detailed Implementation

[0038] To facilitate understanding of this utility model, a more comprehensive description of this utility model will be given below with reference to the accompanying drawings.

[0039] Please see Figure 1 , Figure 2 , Figure 3 and Figure 4 As shown, a nickel-zinc battery with a degassing structure includes: a battery body 100 and a degassing structure 200. The battery body 100 includes a battery core 110, which has a winding cavity 111. The degassing structure 200 is built into the winding cavity 111 and has a hydrogen-oxygen composite catalyst 200a on it. The hydrogen-oxygen composite catalyst 200a is used to catalyze the hydrogen and oxygen generated inside the battery body 100 to undergo a composite reaction to generate water.

[0040] It should be noted that nickel-zinc batteries are prone to gas evolution side reactions during charging and discharging, mainly caused by water decomposition in the electrolyte and electrode side reactions, primarily producing hydrogen and oxygen. The accumulation of these gases leads to increased internal battery pressure and electrolyte drying, affecting battery cycle performance. In severe cases, it can even cause battery casing expansion and leakage. Therefore, in this invention, a degassing structure 200 is added to the nickel-zinc battery to eliminate hydrogen and oxygen, while simultaneously catalytically reacting the hydrogen and oxygen to produce water to replenish the electrolyte. Specifically, the battery manufacturing process typically involves a winding process, where stacked positive electrode sheets, separator sheets, and negative electrode sheets are wound together using a winding needle and equipment to form a battery core 110. Taking a cylindrical nickel-zinc battery as an example, after the winding process is completed, the winding needle needs to be removed from the battery core 110, leaving a cavity. This cavity is usually not fully utilized, resulting in wasted internal battery space. Depending on the cylindrical battery model, such as AAA, AA, SubC, D, and F, the diameter of its core cavity can be between 2 and 8 mm. Therefore, by fully utilizing this cavity, the degassing structure 200 containing the hydrogen-oxygen composite catalyst 200a can be embedded within the winding cavity 111. Utilizing the catalytic activity of the hydrogen-oxygen composite catalyst 200a, the hydrogen and oxygen generated during the battery's charging and discharging process, from water decomposition in the electrolyte and electrode side reactions, can undergo a recombination reaction under the action of the hydrogen-oxygen composite catalyst 200a, thereby converting the gas into liquid water. In this way, not only can the accumulated hydrogen and oxygen inside the nickel-zinc battery be eliminated, preventing the casing 120 from expanding, cracking, or the battery's cycle performance from deterioration due to gas buildup inside the nickel-zinc battery; at the same time, the water molecules produced by the catalytic reaction of hydrogen and oxygen can also flow back into the electrolyte, replenishing the water consumed by the electrolyte, maintaining the electrolyte's ion transport capacity, and greatly extending the battery's cycle life; in addition, the degassing structure 200 is built into the winding cavity 111 of the battery core 110, without occupying additional external space of the battery, thus achieving both the battery's degassing function and the battery's miniaturization design.

[0041] Specifically, the positive electrode of a nickel-zinc battery is made by uniformly coating spherical nickel hydroxide, metallic nickel powder, functional oxide additives (such as zinc oxide (ZnO), tungsten oxide (WO3), magnesium oxide (MgO), yttrium oxide (Y2O3), cobalt(II) oxide (CoO), cobalt tetroxide (Co3O4), and lanthanum oxide (La2O3)), and binders (such as polytetrafluoroethylene (PTFE) emulsion, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) emulsion) onto a foamed nickel current collector using dry or wet processes. The bulk phase of the spherical nickel hydroxide can be doped with elements such as cobalt (Co), manganese (Mn), yttrium (Y), zinc (Zn), tungsten (W), and lanthanum (La). The surface of the spherical nickel hydroxide can be coated with cobalt hydroxide (Co(OH)2) or yttrium hydroxide (Y(OH)3). The negative electrode is made by uniformly coating nano-zinc oxide, metallic zinc powder, functional oxide additives (such as titanium dioxide (TiO2), silicon dioxide (SiO2), aluminum oxide (Al2O3), bismuth oxide (Bi2O3), cerium dioxide (CeO2), tin dioxide (SnO2), indium oxide (In2O3), calcium oxide (CaO), lead oxide (PbO)), and binders (such as polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, sodium polyacrylate) onto the surface of porous tin-plated copper foil, copper foil current collector, or zinc foil current collector using a wet process. The nano-zinc oxide has a purity of ≥99.99% and a particle size D50 range of 100-800 nm. The metallic zinc powder can be doped with elements such as indium (In), bismuth (Bi), aluminum (Al), calcium (Ca), and silicon (Si), with a particle size D50 range of 10-100 μm. The separator is a composite of porous non-woven fabric and microporous polymer membrane, possessing good hydrophilicity, alkali resistance, and thermal stability. It can be used to absorb alkaline electrolytes and prevent zinc dendrite growth from puncturing the separator and causing a short circuit. Alkaline electrolytes are prepared by dissolving alkaline compounds (such as sodium hydroxide (NaOH), lithium hydroxide (LiOH), potassium hydroxide (KOH), etc.) in water to obtain an alkaline electrolyte suitable for nickel-zinc batteries. The electrolyte concentration is as high as 30-55 wt.%, and it may contain organic additives (such as hexadecyltrimethylammonium bromide, triethanolamine, polyethylene glycol, polyvinyl alcohol) or inorganic additives (such as aluminum hydroxide (Al(OH)3), calcium hydroxide (Ca(OH)2), sodium silicate (Na2SiO3)). Due to gas evolution side reactions, the consumption of water molecules in the electrolyte can severely affect the electrolyte concentration, even causing the electrolyte to dry out, and in severe cases, the discharge capacity may plummet.

[0042] Furthermore, the degassing structure 200 containing the hydrogen-oxygen composite catalyst 200a has two implementation methods:

[0043] Please see Figure 4As shown, the first embodiment of the degassing structure 200 includes a support 210, on which a hydrogen-oxygen composite catalyst 200a is disposed. The support 210 serves as a substrate to support the hydrogen-oxygen composite catalyst 200a. For example, processes such as coating, impregnation, or ultrasonic spraying can be used to adhere the hydrogen-oxygen composite catalyst 200a to the surface of the support 210. Thus, the support 210 is used to immobilize the hydrogen-oxygen composite catalyst 200a, thereby reducing the risk of hydrogen-oxygen composite catalyst 200a particles detaching and contaminating the electrolyte. In this embodiment, the support 210 is made of an alkali-resistant material, such as polyethylene, polypropylene, polytetrafluoroethylene, nylon, polyvinyl chloride, polyvinylidene fluoride, fluororubber, or perfluoroether rubber. Polytetrafluoroethylene (PTFE) has good hydrophobicity and chemical stability. Therefore, PTFE is preferred for the carrier 210. This can prevent water molecules from adhering to the carrier 210 and allow the generated liquid water molecules to flow back into the battery core, where they can continue to participate in the electrochemical reaction during the charging and discharging process.

[0044] Furthermore, in this embodiment, the support 210 has a tubular structure. That is, the support 210 adopts a hollow tubular structure, and both ends of the tubular structure are not closed, which facilitates the introduction of gas and the outflow of water molecules from both ends of the support 210. In addition, the tubular support 210 has an inner sidewall and an outer sidewall, and the hydrogen-oxygen composite catalyst 200a is attached to the inner sidewall and / or the outer sidewall. That is, there are three attachment positions for the hydrogen-oxygen composite catalyst 200a: the first is to attach it only to the outer sidewall of the support 210; the second is to attach it only to the inner sidewall of the support 210; and the third is to attach the hydrogen-oxygen composite catalyst 200a to both the inner and outer sidewalls of the support 210. Since the attachment area of ​​the hydrogen-oxygen composite catalyst 200a in the third type is the largest, it can greatly increase the contact area between the gas and the hydrogen-oxygen composite catalyst 200a and improve the conversion efficiency. Therefore, the attachment method of the hydrogen-oxygen composite catalyst 200a is preferably the third type.

[0045] Please see Figure 5 As shown, in a second embodiment of the degassing structure 200, the hydrogen-oxygen composite catalyst 200a is formed into a support 210 through a granulation process. That is, the hydrogen-oxygen composite catalyst 200a is directly formed into the support 210 (the catalyst itself constitutes the main structural component) through a granulation process, possessing both catalytic and structural support functions. This greatly increases the contact area between the gas and the catalyst. In this embodiment, the support 210 also has a tubular structure, further increasing the contact area between the gas and the catalyst and enhancing the gas recombination reaction.

[0046] Furthermore, regardless of whether the hydrogen-oxygen composite catalyst 200a is attached to the surface of the support 210 as a substrate, or whether the hydrogen-oxygen composite catalyst 200a is directly granulated into the support 210, the support 210 can have the following structure:

[0047] In one embodiment, the support 210 has multiple vent holes 211 on its sidewall. Since the support 210 has a tubular structure, the vent holes 211 connect with the hollow cavity of the support 210, facilitating gas entry through the vent holes 211 onto the inner sidewall of the support 210 and contact with the hydrogen-oxygen composite catalyst 200a on the inner sidewall. This further promotes room-temperature catalytic composite reaction of the gas on the surface of the hydrogen-oxygen composite catalyst 200a. In this embodiment, the diameter of the vent holes 211 is 0.1mm-2mm. The size of the vent holes 211 can be selected to match the size of the battery, while ensuring smooth gas flow and preventing the vent holes 211 from becoming too small and clogging.

[0048] In one embodiment, the shape and structure of the outer contour of the cross-section of the carrier 210 are adapted to the shape and structure of the cross-section of the wound cavity 111.

[0049] It should be noted that by adapting the outer contour of the cross-section of the support 210 to the shape and structure of the winding cavity 111, the gap between them can be reduced, allowing the degassing structure 200 to fit more tightly with the winding cavity 111. This tightly fitted structure not only ensures that almost all the gas within the winding cavity 111 passes through the catalyst on the surface of the support 210, improving gas catalytic efficiency, but also prevents the support 210 from shaking within the winding cavity 111, reducing the risk of structural wear or catalyst detachment due to vibration.

[0050] Furthermore, since the cross-sectional shape of the winding needle is typically circular, elliptical, or polygonal, the cross-section of the resulting winding cavity 111 is also circular, elliptical, or polygonal. Therefore, the shape of the outer contour of the cross-section of the support 210 is also circular, elliptical, or polygonal. In this embodiment, the maximum dimension of the outer contour of the cross-section of the support 210 is 2mm-8mm, which is compatible with the size of the conventional nickel-zinc battery winding cavity 111. It should be noted that when the support 210 serves as a substrate to attach the hydrogen-oxygen composite catalyst 200a to its surface, the maximum dimension of the outer contour of the cross-section of the support 210 includes the thickness of the hydrogen-oxygen composite catalyst 200a layer.

[0051] In another embodiment of the battery winding, see [reference needed]. Figure 7As shown, there is a vertical diaphragm piece B in the winding cavity 111. This is because the winding needle used is usually divided into upper and lower metal rods. During the winding process, the initial end of the diaphragm piece needs to be pre-wound by the upper and lower metal rods, that is, the diaphragm piece needs to be pre-wound to avoid problems such as positional displacement during the winding process. Therefore, if no treatment is done, a portion of the vertical diaphragm piece B will usually remain in the winding cavity 111 after the winding needle is removed. Therefore, please refer to... Figure 8 As shown, a degassing structure 200 is applied to the aforementioned battery core. A clearance groove 212 is provided on the degassing structure 200 to avoid the diaphragm B erected at the core cavity 111, allowing the degassing structure 200 to be inserted into the core cavity 111. Alternatively, the degassing structure 200 can be divided into two halves, with each half placed on either side of the erected diaphragm B. In one embodiment, the hydrogen-oxygen composite catalyst 200a is a supported catalyst, a hydrophobic supported catalyst, a porous support supported catalyst, or a hydrophobic porous support supported catalyst. Specific descriptions of different hydrogen-oxygen composite catalysts are as follows:

[0052] Supported catalysts: Noble metal catalysts (e.g., platinum (Pt), palladium (Pd), rhodium (Rh), platinum-ruthenium alloy (PtRu)) or non-precious metal catalysts (e.g., copper (Cu), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), molybdenum (Mo)) are used as active components and are fixed on the surface or in the pores of a support through loading (e.g., impregnation, precipitation, physical adsorption). Noble metal catalysts are supported on carbon materials (e.g., activated carbon, carbon nanotubes, graphene, acetylene black, etc.); non-noble metal catalysts are supported on metal oxides (e.g., aluminum oxide (Al2O3), silicon dioxide (SiO2), titanium dioxide (TiO2), tin dioxide (SnO2), magnesium oxide (MgO), tungsten trioxide (WO3), etc.), nitrides (e.g., boron nitride (BN), aluminum nitride (AlN), titanium nitride (TiN), etc.), carbides (e.g., silicon carbide (SiC), titanium carbide (TiC), chromium carbide (Cr3C2), tungsten carbide (WC), etc.) or sulfides (e.g., molybdenum disulfide (MoS2), nickel sulfide (Ni3S2), etc.).

[0053] By using supported catalysts, the aggregation of active ingredients can be avoided. At the same time, the high specific surface area of ​​the support can be used to improve the dispersibility of active ingredients. This not only improves the conversion efficiency but also reduces the amount of precious metals used and lowers the material cost.

[0054] It should be noted that, to balance the cost and catalytic performance of the degassing structure, the active ingredient can be a nanocatalyst with a small particle size and high specific surface area. The particle size range of the noble metal catalyst is 10-200 nm, and its content can be 0.01-1 wt.%, while the particle size range of the non-noble metal catalyst is 100-500 nm, and its content can be 0.5-5 wt.%. For the selection of carbon material supports, graphene, multi-walled carbon nanotubes, or single-walled carbon nanotubes with hydrophobic properties and high specific surface area are preferred. To further reduce costs, metal oxide supports can be considered, with aluminum oxide (Al₂O₃), silicon dioxide (SiO₂, e.g., MCM-41, SBA-15), titanium dioxide (TiO₂), and magnesium oxide (MgO) being preferred materials.

[0055] Hydrophobic supported catalysts: These are catalysts based on which a hydrophobic support is introduced or a hydrophobic component (such as polytetrafluoroethylene (PTFE), polypropylene (PP), polyethylene (PE), polyvinylidene fluoride (PVDF), polyvinyl chloride (PVC), fluororubber (FKM), polyphenylene sulfide (PPS), and other plastic microspheres) are added. The hydrophobic support has low surface energy, which effectively reduces the adhesion of water generated in the reaction to the catalyst surface, preventing a water film from covering the active sites. This promotes the detachment of water molecules from the catalyst, reducing the retention rate of water molecules on the catalyst surface, and simultaneously facilitates the return of water molecules to the electrolyte, replenishing the water molecules consumed in the electrolyte, thereby improving the cycle life and charge-discharge performance of nickel-zinc batteries.

[0056] Porous support-supported catalyst: This refers to a supported catalyst with a porous support having a perforated structure, which facilitates the return of water molecules to the separator of the battery core 110. In particular, the support 210 formed by granulation of the hydrogen-oxygen composite catalyst 200a, which includes a porous support with a perforated structure, allows water molecules to penetrate the sidewalls of the support 210 and flow back to the separator of the battery core 110.

[0057] Hydrophobic porous support supported catalyst: That is, based on the supported catalyst, the dual characteristics of hydrophobic support and hollow structure porous support are introduced at the same time. The hydrophobicity promotes the rapid detachment of water molecules generated by the reaction from the catalyst and can also prevent the pores from being blocked by water. At the same time, the hydrophobicity combined with the hollow structure makes it easier for water to flow back to the separator of the battery core 110.

[0058] It should be noted that the inner side of the winding cavity 111 formed during the winding process of the battery cell is mainly composed of hydrophilic diaphragms (see reference). Figure 7As shown at point B, the battery cell is pre-wound with a diaphragm sheet reserved at the initial end of the winding. After winding, a diaphragm sheet layer is formed on the inner wall of the winding cavity 111 of the battery cell. This helps to return the liquid water molecules formed by the combination of hydrogen and oxygen to the diaphragm of the battery core 110, thereby replenishing the water in the consumed electrolyte.

[0059] It should also be noted that the following can be consulted: Figure 6 As shown, when it is necessary to embed the degassing structure 200 into the winding cavity 111 of the nickel-zinc battery, the degassing structure 200 can be placed into the insulating cavity using an insulating thin wire A.

[0060] The embodiments described above are merely illustrative of several implementations of this utility model, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the utility model patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this utility model, and these all fall within the protection scope of this utility model. Therefore, the protection scope of this utility model patent should be determined by the appended claims.

Claims

1. A nickel-zinc battery with a degassing structure, characterized in that, include: A battery body, the battery body including a battery core, the battery core having a winding cavity; and The degassing structure is built into the winding cavity and has a hydrogen-oxygen composite catalyst. The hydrogen-oxygen composite catalyst is used to catalyze the hydrogen and oxygen generated inside the battery body to undergo a composite reaction to generate water.

2. The nickel-zinc battery with a degassing structure according to claim 1, characterized in that, The degassing structure includes a support body, and the hydrogen-oxygen composite catalyst is disposed on the surface of the support body, or the hydrogen-oxygen composite catalyst is formed into the support body by a granulation process.

3. The nickel-zinc battery with a degassing structure according to claim 2, characterized in that, The carrier has a tubular structure.

4. The nickel-zinc battery with a degassing structure according to claim 3, characterized in that, The support has an inner wall and an outer wall, and the hydrogen-oxygen composite catalyst is attached to the inner wall and / or the outer wall.

5. The nickel-zinc battery with a degassing structure according to claim 3, characterized in that, The side wall of the carrier has multiple ventilation holes.

6. The nickel-zinc battery with a degassing structure according to claim 5, characterized in that, The diameter of the vent is 0.1mm-2mm.

7. The nickel-zinc battery with a degassing structure according to claim 2, characterized in that, The shape and structure of the outer contour of the cross-section of the carrier are adapted to the shape and structure of the cross-section of the wound cavity.

8. The nickel-zinc battery with a degassing structure according to claim 7, characterized in that, The shape and structure of the outer contour of the cross-section of the carrier can be circular, elliptical, or polygonal.

9. The nickel-zinc battery with a degassing structure according to claim 8, characterized in that, The maximum outer dimension of the cross-section of the carrier is 2mm-8mm.

10. The nickel-zinc battery with a degassing structure according to any one of claims 1-9, characterized in that, The hydrogen-oxygen composite catalyst is a supported catalyst, a hydrophobic supported catalyst, a porous supported catalyst, or a hydrophobic porous supported catalyst.